1980
DOI: 10.1042/bj1850775
|View full text |Cite
|
Sign up to set email alerts
|

Novel inhibitors of poly(ADP-ribose) synthetase

Abstract: In a search for new inhibitors of the nuclear enzyme poly(ADP-ribose) synthetase, it was found that various benzamides substituted in the 3-position were the most inhibitory compounds found to date. Two of the benzamides, 3-aminobenzamide and 3-methoxybenzamide, were found to be competitive inhibitors, with Ki values or less than 2 microM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
197
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(202 citation statements)
references
References 14 publications
2
197
0
1
Order By: Relevance
“…This could be explained by the fact that NAM is a weak PARP inhibitor, whereas NA has no effect on PARP activity. 88 A protective effect of NAM against apoptosis was also demonstrated in the in vivo studies of Klaidman et al 89 and Mukherjee et al, 90 who showed that NAM treatment prevented neuronal apoptosis produced by tertiary-butylhydroperoxide, 89 an organic peroxide, and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, 90 a neurotoxin. A major finding of the present study was that both NA and NAM decreased NF-kB, as measured by a decrease in the activated form of NF-kB and a decrease in protein expression of the NF-kB(p50) and NF-kB(p65) proteins.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This could be explained by the fact that NAM is a weak PARP inhibitor, whereas NA has no effect on PARP activity. 88 A protective effect of NAM against apoptosis was also demonstrated in the in vivo studies of Klaidman et al 89 and Mukherjee et al, 90 who showed that NAM treatment prevented neuronal apoptosis produced by tertiary-butylhydroperoxide, 89 an organic peroxide, and 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, 90 a neurotoxin. A major finding of the present study was that both NA and NAM decreased NF-kB, as measured by a decrease in the activated form of NF-kB and a decrease in protein expression of the NF-kB(p50) and NF-kB(p65) proteins.…”
Section: Discussionmentioning
confidence: 77%
“…An increase in ability to repair DNA is suggested by the role of NAD + as a substrate for PARP, a DNA repair enzyme, and the induction of GAPDH, which also functions in DNA repair through its uracil glycosylase activity. We have previously reported 27 that PARP is protective against apoptosis, since 3-aminobenzamide, a strong PARP inhibitor, 88 sensitized cells to NaDOC-induced apoptosis. In the present study, we found that both NAD + precursors were effective at preventing apoptosis, with NA consistently showing a greater protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 6( reduction in WBC counts were similarly affected by changes in nicotinamide dose as reported for the other endpoints shown in Figure 6. Since 3-aminobenzamide is a more efficient inhibitor of ADPRT than nicotinamide (Purnell & Whish, 1980), we repeated these experiments with this compound. The results are shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…A range of PADPRP inhibitors, of which 3-aminobenzamide (3AB) has been the most widely used, was first developed by Purnell and Whish (1980). The demonstration that they could modulate cellular DNA repair and survival responses (Durkacz et al, 1980) al., 1992).…”
mentioning
confidence: 99%